The Impact of Pre-Retirement Occupational Characteristics on Social Participation in Later Life: A Life Course Perspective - Juanjuan Sun; Kexin Sun (Social Sciences)
Enhancing older adults’ social participation constitutes a critical strategy for actively addressing population aging. From a life course perspective, this study uses data from the 2023 China Longitudinal Aging Social Survey to analyze the impact of occupational characteristics of the pre-retirement of Chinese older adults on their social participation in later life through linear probability models and Logit regression analysis. Key findings reveal that the pre-retirement work sector, occupational roles, and job intensity significantly influence older adults’ social participation. Older adults who previously worked in the public sector are less likely to participate in labor and recreational activities than their non-public sector counterparts. Those who held managerial positions before retirement exhibit higher probabilities of volunteering and recreational activity participation than non-managerial retirees. Additionally, greater pre-retirement job intensity correlates with reduced likelihoods of volunteering and recreational activity participation. Thus, this study identifies inadequate social security provisions as the primary endogenous driver for labor participation in later life. In China’s current developmental phase, gradually delaying the legal retirement age could effectively boost labor supply. Ensuring comprehensive labor protections throughout occupational trajectories and developing tailored interventions based on pre-retirement occupational characteristics prove essential for advancing social participation among older adults. Furthermore, improving information accessibility and participation opportunities serves as crucial pathways for transforming older adults’ participation willingness into concrete behavioral outcomes.